2018
DOI: 10.1007/s40519-018-0629-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of emotional intelligence on disorder eating psychopathology

Abstract: Purpose This study aims to explore the role of Emotional Intelligence (EI) and specific facets that may underpin the aetiology of disordered eating attitudes and behaviours, as a means to understand what aspects of these deficits to target within treatments. Methods Participants were recruited from the UK and Ireland. Among the sample of 355 participants, 84% were women and 16% were men. Regarding age, 59% were between 18 and 29, 30% were between 30 and 49, and 11% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
4
0
3
Order By: Relevance
“…From AEI literature, individuals with high AEI would be better equipped to deal with emotional difficulties. People with a lower score on AEI are more likely to engage in maladaptive emotional regulation strategies [ 20 ], such as disordered eating behaviour. Accordingly, females with an ED have been found to report more maladaptive emotion-focused strategies than their non-clinical counterparts, whilst the ability to regulate emotion has been negatively associated with disordered eating patterns [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…From AEI literature, individuals with high AEI would be better equipped to deal with emotional difficulties. People with a lower score on AEI are more likely to engage in maladaptive emotional regulation strategies [ 20 ], such as disordered eating behaviour. Accordingly, females with an ED have been found to report more maladaptive emotion-focused strategies than their non-clinical counterparts, whilst the ability to regulate emotion has been negatively associated with disordered eating patterns [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, an emerging line of research has typically shown the significant relationship between EI and ED symptoms. For example, some prior research has found that individuals with some EI deficits are more prone to display disordered eating attitudes and behaviors (Costarelli et al, 2009;Pettit et al, 2009;Filaire et al, 2010;Zysberg and Rubanov, 2010;Hambrook et al, 2012;Zavala and López, 2012;Zysberg, 2013;Zysberg and Tell, 2013;Gardner et al, 2014;Koch and Pollatos, 2015;Cuesta et al, 2017;Peres et al, 2018;Foye et al, 2019). In addition, recent systematic reviews have reported that these abilities are relevant factors in both the development and maintenance of ED (Romero-Mesa et al, 2020;Giusti et al, 2021).…”
Section: Emotional Intelligence and Eating Disordersmentioning
confidence: 99%
“…Las mujeres e hijos únicos son quienes presentan con mayor frecuencia esta conducta (Banna et al, 2018;Gow et al, 2016;Mason et al, 2018;Wu et al, 2018). Además, el bajo nivel de inteligencia emocional (reconocimiento, expresión o control de emociones) propicia la alimentación emocional (Foye et al, 2019;Koike et al, 2018), la cual se relaciona positivamente con el índice de masa corporal (Shriver et al, 2019).…”
Section: Afecto Relacionado Con La Acciónunclassified